ICF domains covered by the Tinnitus Questionnaire and Tinnitus Functional Index. Issue 22 (23rd October 2022) - van der Wal, Annemarie; Michiels, Sarah; De Pauw, Joke; Jacxsens, Laura; Chalimourdas, Antonios; Gilles, Annick; Braem, Marc; van Rompaey, Vincent; Van de Heyning, Paul; De Hertogh, Willem
Abstract: Purpose: Tinnitus frequently causes disability as it affects daily living, which is objectified using several tinnitus questionnaires. To what extent they cover domains of the International Classification of Functioning, Disability and Health (ICF) is currently unknown. Therefore, this study aims to investigate which ICF domains are measured by two questionnaires and to describe the health status of somatic tinnitus patients in ICF terms. Materials and methods: All questions of the Tinnitus Questionnaire (TQ) and Tinnitus Functional Index (TFI) were linked to the ICF using linking rules. A count-based method was used to link all individual answers of 80 tinnitus patients, to the ICF categories. Results: Most of the linked questions concerned "body functions". TFI covered more categories of "activity and participation" than TQ. Patients reported severe impairments in "mental functions", "sensory functions and pain", and "sleep functions". Additionally, severe limitations were scored in "focusing attention". Conclusions: The TFI and TQ measure distinct domains but can be used complementary or solely, depending on the research question. The TFI identifies a broad spectrum of problems, where the TQ focuses on the psychological impact of tinnitus. Somatic patients in our study reported impairments and disabilities in all covered domains, especially in "onset of sleep" and "sound detection". Implications for Rehabilitation: The Tinnitus Functional Index (TFI) and the Tinnitus Questionnaire (TQ) cover different domains of the International Classification of Functioning, Disability and Health. The TFI identifies problems in "body functions" and "activity and participation". The TQ focuses on the psychological impact of tinnitus.